Effect of Testosterone Synthesis and Conversion on Serum Testosterone Levels in Obese Men - Xu, Xiaolin; Wang, Lei; Luo, Dandan; Zhang, Meijie; Chen, Shuhong; Wang, Yupeng; Zheng, Dongmei; Feng, Li; Gao, Ling; Yu, Chunxiao; Guan, Qingbo (Hormone and Metabolic Research, 2018)
Obesity is associated with decreased testosterone levels in males. Testosterone is synthesized by testosterone synthetic enzymes, which are stimulated by luteinizing hormone (LH). Testosterone can also be converted to estradiol via the aromatase. The objective of this study was to examine the factors related to testosterone synthesis and conversion, and to systematically evaluate the key processes that influence testosterone levels in male obesity. Three hundred and two male subjects (aged 25–45 years old) were divided according to BMI into normal weight (18.5–23.9 kg/m2), overweight (24–27.9 kg/m2), and obese (≥28 kg/m2) groups; or divided following WHR into non-abdominal obesity and abdominal obesity groups (WHR: ≥0.9). Male C57BL/6 mice were divided into normal diet (ND) and high-fat diet (HFD)-induced obesity group. Serum sex hormones and aromatase levels were measured using ELISAs. Testosterone synthetic enzymes in the testes were measured by qRT-PCR. The testosterone levels in obese men and abdominal obesity men were lower than normal men. In abdominal obesity men serum LH levels were decreased and associated with testosterone levels after multivariate regression analysis. Serum aromatase levels were increased in abdominal obesity males. In mice, compared to the ND group, the HFD group had decreased steroidogenic acute regulatory protein (StAR). However, aromatase levels in subcutaneous adipose tissue were higher in the ND group than HFD group. In conclusion, according to this study decreased testicular synthesis function and the conversion of testosterone may explain the reduction in testosterone levels in male obesity, and the decrease of testicular synthesis may change first.
Keywords: aromatase; male; obesity; StAR; testosterone